A survey of contemporary economics - Haley, Bernard Francis; American Economic Association (Homewood, Ill. : R.D. Irwin, for the American Economic Association, 1952)
This volume continues the experiment, sponsored by the American Economic Association. The primary purpose of the experiment has been to test the usefulness of a periodic review of developments in the different fields of economics.
Volume 2.
Includes bibliographical footnotes and index.
ne 23/01/2019
Loans
Keywords: Economics